Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1093/nar/gky300
|View full text |Cite
|
Sign up to set email alerts
|

DynaMut: predicting the impact of mutations on protein conformation, flexibility and stability

Abstract: Proteins are highly dynamic molecules, whose function is intrinsically linked to their molecular motions. Despite the pivotal role of protein dynamics, their computational simulation cost has led to most structure-based approaches for assessing the impact of mutations on protein structure and function relying upon static structures. Here we present DynaMut, a web server implementing two distinct, well established normal mode approaches, which can be used to analyze and visualize protein dynamics by sampling co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
672
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 835 publications
(734 citation statements)
references
References 47 publications
8
672
0
Order By: Relevance
“…The different residues located near the inter‐domain region could be responsible for the slightly different conformations of both chitinases, the differences in the kinetic properties and also the different thermodynamic parameters, which could promote divergence in the formation of the protein–ligand complex. In this regard, it has been recognized that mutations can exert long‐distance effects on protein structure, flexibility and stability . Finally, we also demonstrated that both enzymes, one of which (AtChi2) was obtained from RNA of F. oxysporum‐ infected plants, exhibit antifungal activity versus Aspergillus sp.…”
Section: Discussionmentioning
confidence: 53%
“…The different residues located near the inter‐domain region could be responsible for the slightly different conformations of both chitinases, the differences in the kinetic properties and also the different thermodynamic parameters, which could promote divergence in the formation of the protein–ligand complex. In this regard, it has been recognized that mutations can exert long‐distance effects on protein structure, flexibility and stability . Finally, we also demonstrated that both enzymes, one of which (AtChi2) was obtained from RNA of F. oxysporum‐ infected plants, exhibit antifungal activity versus Aspergillus sp.…”
Section: Discussionmentioning
confidence: 53%
“…The coordinates were submitted to the DynaMut server for analysis. 24 For molecular dynamics (MD), allatom models of human TMEM175 were constructed with MODELLER, 25 using the crystal structure of Chamaesiphon minutus TMEM175 channel 26 (protein data bank ID: pdb 5VRE) as a template. For chain A and chain B, residues 36 to 230 and 261 to 473 were aligned using LOMETS 27 ; this returns 10 pairwise alignments, which we combined into a single alignment for which no gaps were introduced in alpha-helices (see Fig 1A).…”
Section: Homology Modeling and Molecular Dynamics Simulationsmentioning
confidence: 99%
“…The arginine-323 to methionine mutation was modeled by selecting the most probable rotamer conformation according to the Richardson backbone-independent rotamer library (Lovell et al 2000). The predicted effects of the R323C mutation on TRMT1 structure was performed using DynaMut (Rodrigues et al 2018).…”
Section: In Silico Analysis Of Trmt1 Structurementioning
confidence: 99%